2017
DOI: 10.1371/journal.pone.0182360
|View full text |Cite
|
Sign up to set email alerts
|

A journey without maps—Understanding the costs of caring for dependent older people in Nigeria, China, Mexico and Peru

Abstract: Purpose of the studyPopulations in Latin America, Asia and sub-Saharan Africa are rapidly ageing. The extent to which traditional systems of family support and security can manage the care of increased numbers of older people with chronic health problems is unclear. Our aim was to explore the social and economic effects of caring for an older dependent person, including insight into pathways to economic vulnerability.Design & methodsWe carried out a series of household case studies across urban and rural sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 26 publications
0
62
0
4
Order By: Relevance
“…The results suggest that in an effort to improve adaptation to heavy stressors of families of patient with dementia, future interventions should target improving different sources of support, especially FA and kin support. Several studies have shown that in families in which adult children are primary caregivers, adult children will have difficulty balancing the physical and financial needs of multiple roles, 17,19 which affected family relationships and FA. Studies of Zairt and Bangerter have also shown that most of the families have conflicts related to caregiving.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggest that in an effort to improve adaptation to heavy stressors of families of patient with dementia, future interventions should target improving different sources of support, especially FA and kin support. Several studies have shown that in families in which adult children are primary caregivers, adult children will have difficulty balancing the physical and financial needs of multiple roles, 17,19 which affected family relationships and FA. Studies of Zairt and Bangerter have also shown that most of the families have conflicts related to caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…So, we also confirmed that FA and kin support were mediators through our research at the same time. As many studies have shown, the heavy burden of stressor in families of patients with dementia led to conflicts among family members and relatives, [16][17][18][19] which reduced the FA and kin support. And the support influenced family adaptation in turn.…”
Section: Effect Of Community Support and N-social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…At the incidence wave survey, assets were similarly distributed between households selected for ‘care’ and ‘no care’ groups [ 24 ]. The accompanying qualitative case studies enabled us to explore mechanisms underlying any observed associations between care dependence and household impoverishment, including factors that support economic resilience [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our current findings, a recent systematic review of qualitative studies from LMICs showed that loneliness was often characterised by older people as loss: of physical functioning, independence, close confidantes, social participation and sense of belonging within families and societies [20,22,23]. Results from the 10/66 DRG INDEP study and a recent study in Ghana carried out among dependent older people suggest that changing societal expectations (greater female participation in paid employment, longer periods of education for young people) were putting a strain on social norms of intergenerational reciprocity [45,46].…”
Section: Discussionmentioning
confidence: 99%